1990
DOI: 10.1021/tx00013a007
|View full text |Cite
|
Sign up to set email alerts
|

Laser spectroscopic studies of DNA adduct structure types from enantiomeric diol epoxides of benzo[a]pyrene

Abstract: A methodology based on 77 K laser-excited fluorescence spectroscopy, fluorescence quenching, and fluorescence line narrowing is shown to be a highly selective and sensitive approach for the study of polycyclic aromatic carcinogen-DNA complexes. Three and five different DNA adducts derived from (+)-trans-7,8-dihydroxy-anti-9,10-epoxy-7,8,9,10-tetrahydrobenzo [a]pyrene and its (-)-enantiomer are identified, respectively. Two different methods are used to classify the adducts as type I (interior) or type II (exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
61
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 17 publications
15
61
0
Order By: Relevance
“…The multiple zero phonon lines observed are characteristic of the corresponding vibrational modes. It has also been noted earlier (11,19) that the covalent interactions of the carcinogen benzo[alpyrene with protein and DNA causes large relative changes in the intensities of zero phonon lines but changes the frequency of the vibrational modes only marginally.…”
Section: Pagementioning
confidence: 62%
See 2 more Smart Citations
“…The multiple zero phonon lines observed are characteristic of the corresponding vibrational modes. It has also been noted earlier (11,19) that the covalent interactions of the carcinogen benzo[alpyrene with protein and DNA causes large relative changes in the intensities of zero phonon lines but changes the frequency of the vibrational modes only marginally.…”
Section: Pagementioning
confidence: 62%
“…At 368-nm excitation, however, the spectra of adducted H3 appeared to be red shifted and broad ( Figure 4). This anomalous behavior is not well understood but could be the result of a stronger interaction of the pyrene with the protein, leading to broadening and red shifting of the lines (19). These effects are not responsible, though, for the apparent broad peak at 382 nm in Figures 3 and 4, which is a phonon wing.…”
Section: Pagementioning
confidence: 94%
See 1 more Smart Citation
“…Furthemiore, the biological activity-structure relationships can be illustrated by using aforementioned methodology [171,183].…”
Section: F Interaction Between Bpt and Dna In Solid Water And Glass mentioning
confidence: 99%
“…In general,the trans configuration is characterized as site type H, whereas cis adduct is classified as site type I. Even though the carcinogen interacts less strongly with bases of oligonuleotides in (±)-2' than in (±)-3, which were previuosly assigned as site I [171,183], all the basestacking properties of the (-)-2' conformation allow this adduct to be assigned as site type I. This (-)-2' conformation of (-)-franj-BPDE-d(CACATGTACAC)2, identified here for the first time, may be responsible for the disagreement in configuration-conformation relationship observed by Geacintov et al [186], where they observed that the ratio of cis to trans was ~1.7, whereas the ratio of site I to site U was ~9.…”
Section: F Interaction Between Bpt and Dna In Solid Water And Glass mentioning
confidence: 99%